Comparison Model of Vegetation Index and Mangrove Density using Landsat 8 Satellite Imagery in Ujungpangkah - Prakoso, Shaktiawan Lawyerrisa; Wibisana, Hendrata (CIVED, 2024)
Gresik Regency is a coastal area with a significant mangrove population, notably in the Ujungpangkah region. The Ujungpangkah mangrove forest is a designated ecotourism and conservation area. However, due to management and utilization practices by the local community, the mangrove ecosystem in Banyuurip Village, Ujungpangkah District, has experienced a decline. This study aims to determine the mangrove density in Banyuurip Village using vegetation index transformation methods (NDVI and DVI). Assessing the density of mangrove vegetation is crucial for the effective management of mangrove forests to ensure they fulfill their ecological functions. The research employs a quantitative method, utilizing Landsat 8 imagery data to measure mangrove density using the NDVI and DVI methods. The study results indicate that the NDVI canopy density classification is 86.67%, divided into three classes: dense (569.700 ha or 95.32%), medium (29.910 ha or 4.50%), and sparse (1.080 ha or 0.18%). Meanwhile, the FCD classification results are 73.33%, also divided into three classes: dense (583.740 ha or 97.67%), medium (13.410 ha or 2.24%), and sparse (0.540 ha or 0.09%). The NDVI method proved to be the most accurate for classifying canopy density based on the accuracy test data